problem43_03

problem43_03 - 43.3: E = z B - (- z B ) = 2 z B hf But E =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: 43.3: E = z B - (- z B ) = 2 z B hf But E = hf , so B = 2 z (6.63 10 -34 J s)(2.27 10 7 Hz) B= = 0.533 T 2(2.7928)(5.051 10 - 27 J T) ...
View Full Document

This note was uploaded on 05/12/2008 for the course PHYS 262 taught by Professor Dougherty during the Spring '08 term at Lafayette.

Ask a homework question - tutors are online